Intracystic Glucose and Carcinoembryonic Antigen in Differentiating Histologically Confirmed Pancreatic Mucinous Neoplastic Cysts. (31st March 2022) - Smith, Zachary L.; Satyavada, Sagarika; Simons-Linares, Roberto; Mok, Shaffer R.S.; Martinez Moreno, Bélen; Aparicio, José Ramón; Chahal, Prabhleen
Abstract : INTRODUCTION: Differentiating mucinous neoplastic pancreatic cysts (MNPC) from cysts without malignant potential can be challenging. Guidelines recommend using fluid carcinoembryonic antigen (CEA) to differentiate MNPC; however, its sensitivity and specificity vary widely. Intracystic glucose concentration has shown promise in differentiating MNPC, but data are limited to frozen specimens and cohorts of patients without histologic diagnoses. This study aimed to compare glucose and CEA concentrations in differentiating MNPC using fresh fluid obtained from cysts with confirmatory histologic diagnoses. METHODS: This multicenter cohort study consisted of patients undergoing endoscopic ultrasound–guided fine-needle aspiration (EUS-FNA) for pancreatic cysts during January 2013–May 2020. Patients were included if the cyst exhibited a histologic diagnosis and if both CEA and glucose were analyzed from fresh fluid. Receiver operating curve (ROC) characteristics were analyzed, and various diagnostic parameters were compared. RESULTS: Ninety-three patients, of whom 59 presented with MNPC, met the eligibility criteria. The area under the receiver operating curve (AUROC) was 0.96 for glucose and 0.81 for CEA (difference 0.145, P = 0.003). A CEA concentration of ≥192 ng/mL had sensitivity of 62.7% and specificity of 88.2% in differentiating MNPC, whereas glucose concentration of ≤25 mg/dL had sensitivity and specificity of 88.1% and 91.2%, respectively. DISCUSSION: Intracystic glucose is superior to CEA concentration for differentiating MNPC when analyzed from freshly obtained fluid of cysts with histologic diagnoses. The advantage of glucose is augmented by its low cost and ease of implementation, and therefore, its widespread adoption should come without barriers. Glucose has supplanted CEA as the best fluid biomarker in differentiating MNPC.